Twitter Ban in Nigeria: A Stigma to Democratic Governance - Rotimi Oluwatosin Goodness; Kester C. Onor; Gyuse Terdoo Sandra; Sheriff F. Folarin (Universitas Medan Area, 2022)
‘Twitter’ in the 21st century has become a useful tool for information gathering, sharing and interactions amongst individuals and for diplomatic negotiations between governments across the world. The potency along the communication lines of twitter lies in its ability to reach a wide and diversified audience quickly and simultaneously. Most intriguing is that individuals through public opinion on twitter hold governments accountable for their actions. With the application of libertarian theory, the prohibition on Twitter in Nigeria is investigated empirically in this study. Drawing on secondary sources of data collection, findings of the study revealed that regardless of the enormous prospects and economic relevance of twitter in Nigeria, the twitter ban is an undemocratic act and an utter infringement on freedom of expression and access to information sharing which constitute fundamental human rights. The study concluded by stating that the Nigerian government should revert the ban on twitter and restore the digital right of Nigerian residents to the platform. The study recommended that democratic institutions should be more consolidated so that the rule of law can be guaranteed. In addition, given that Nigeria is said to be a democratic country, rather than infringing on rights to freedom of speech and expression by control, banning or censoring of social media activities, the Nigerian government can opt for press conferences, press releases and even social media platforms to communicate with a larger crowd on brewing social issues.